The postnatal development of MT, V1, LGN, pulvinar and SC in prosimian galagos (Otolemur garnettii). Issue 17 (24th February 2020) - Turner, Emily C.; Gabi, Mariana; Liao, Chia‐Chi; Kaas, Jon H.
Abstract: Considerable evidence supports the premise that the visual system of primates develops hierarchically, with primary visual cortex developing structurally and functionally first, thereby influencing the subsequent development of higher cortical areas. An apparent exception is the higher order middle temporal visual area (MT), which appears to be histologically distinct near the time of birth in marmosets. Here we used a number of histological and immunohistological markers to evaluate the maturation of cortical and subcortical components of the visual system in galagos ranging from newborns to adults. Galagos are representative of the large strepsirrhine branch of primate evolution, and studies of these primates help identify brain features that are broadly similar across primate taxa. The histological results support the view that MT is functional at or near the time of birth, as is primary visual cortex. Likewise, the superior colliculus, dorsal lateral geniculate nucleus, and the posterior nucleus of the pulvinar are well‐developed by birth. Thus, these subcortical structures likely provide visual information directly or indirectly to cortex in newborn galagos. We conclude that MT resembles a primary sensory area by developing early, and that the early development of MT may influence the subsequent development of dorsal stream visual areas. Abstract : The middle temporal visual area (MT) is revealed by parvalbumin immunoreactivity in early development (P3) of galagos, suggesting that MT resembles the primary sensory areas by developing early, and the early development of MT may influence the subsequent development of dorsal stream visual areas.